Transformations: teaching-learning Process in the 21st Century - YADAV, SAPNA (THE PRIMARY TEACHER, 2014)
The purpose of this paper is to examine the effectiveness of latest techniques in teaching-learning process. We think of the effective teachers we have had over the years with a sense of recognition, but those who have touched our humanity we remember with a deep sense of gratitude. Basically, teaching must include two major components sending and receiving information. Teaching in classroom using chalk and talk is “one way flow” of information. Teachers often continuously talk for an hour without knowing students response and feedback. The material presented in class is only based on lecturer notes and textbooks; there is insufficient interaction with students in classroom. Moreover, emphasis has been given on theory without any practical and real life time situations. So, any communication methods that resolve the purpose without destroying the objective could be considered as innovative methods of teaching. The use of innovative methods in educational institutions has the potential not only to improve education, but also to empower people, strengthen governance and galvanise the effort to achieve the human development goal for the country. Confucius has correctly phrased in this regard: I hear and I forgot. I see and I believe. I do and I understand.